Predictable patterns of unsustainable intensification - Rietveld, Anne M.; Groot, Jeroen C.J.; Burg, Margreet van der (2021)
Poster submitted to NWO conference 2021. To increase understanding of agricultural intensification processes over time and their sustainability, we studied dimensions of sustainability in the context of ongoing expansion of intensive, commercial mono-cropping of banana in Southwestern Uganda. In our approach we considered five dimensions of sustainability: economic, agricultural productivity, environment, social and human. We compared farming systems in 1998 and 2018 and integrated a gender lens. A total of four focus group discussions, two group interviews and fifteen individual interviews (8m / 7f) were conducted, complemented with a discourse analysis of newspaper articles. Results show that although intensification of banana production increased the average income level indicating improvement in the economic dimension, it did not yield sustainable outcomes in the other dimensions. The integrated analysis of five dimensions of sustainability illuminated aspects often neglected in assessment studies or policy-making around agricultural intensification, in particular socioeconomic and gender dynamics. We further recognized that the observed local trends are part of a set of patterns that take place throughout the world. We conclude that to advance sustainable development, stakeholders should move away from the current over-emphasis on economic values prioritizing the individual, and that avoiding patterns of unsustainable development requires broadening to environmental and community values.